Mitogenomic features of three species of Entomobryoidea (Collembola) from China - Godeiro, Nerivania Nunes; Xu, Cong; Zhang, Guoqiang; Zhang, Feng (Zootaxa, 2022)
Three novel mitogenomes of Entomobryoidea were assembled and annotated. Sequences final lengths were 14,683 bp for Alloscopus bannaensis, 14,884 bp for Sinhomidia bicolor, and 14,794 bp for Coecobrya sp., including 13 PCGs, 22 tRNA, and 2 rRNA genes. To confirm the morphological identifications, maximum likelihood and Bayesian analyses were performed and the species were placed in the correct phylogenetic position, except A. bannaensis which support value was low to confirm its placement. All three mitogenomes are the first ones published for these genera, the genetic data generated here will be useful for further phylogenetic analyses of the group Collembola.